Pseudophakic eye with obliquely crossed piggyback toric intraocular lenses - Jin, Haiying; Limberger, Il-Joo; Borkenstein, Andreas; Ehmer, Angela; Guo, Haike; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2010)
A 72-year-old man presented with high astigmatism (2.25 −5.0 × 45) induced by long-term rotation of a toric intraocular lens (IOL). Corneal astigmatism was 3.78 diopters (D). The corrected distance visual acuity (CDVA) was 20/32. Because of the risk of repositioning, a secondary toric IOL of −3.0/6.0 D especially designed for sulcus implantation was piggybacked through 3.5 mm sutureless clear-corneal incision with a cylindrical axis obliquely crossed with that of the primary IOL. Eight months postoperatively, the corneal astigmatism was 5.04 D. The CDVA was 20/25 with a refraction of 1.0 −2.5 × 70. No interlenticular opacification or significant rotation or decentration of the secondary toric IOL was observed. The refractive properties of this pseudophakic eye were analyzed using a mathematical approach. The calculated postoperative refraction was 0.84 −1.7 × 47. A piggyback toric IOL can be implanted in an obliquely crossed style that allows a secondary toric IOL to correct astigmatism induced by long-term toric IOL rotation. - Financial Disclosure: - No author has a financial or proprietary interest in any material or method mentioned.
Gesehen am 24.08.2023